Developing 21st Century Creative Writing Competencies through Edupreneurship and Creativepreneurship in Journalism Education - Nufus, Hayatun; Subyantoro, Subyantoro; Mardikantoro, Hari Bakti; Pristiwati, Rahayu (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study focuses on the development of creative writing enrichment books that incorporate 21st-century competencies within journalism courses, aligning with the principles of edupreneurship and creativepreneurship. The enrichment books are designed to enhance students' creative writing abilities while equipping them with critical skills such as problem-solving, creativity, communication, and digital literacy key competencies required in the modern media landscape. Employing a Research and Development (R&D) approach, the study implemented the enrichment books across multiple universities. Initial assessments (pre-tests) indicated that students’ creative writing proficiency was at a "Fair" level, with an average score of 46%. However, after utilizing the enrichment books, post test results showed a significant improvement, with an average score rising to 91%, classified as "Very Good". These findings highlight the effectiveness of integrating creative writing enrichment books with 21st-century competencies in enhancing students' writing skills. Additionally, the study underscores the crucial role of technology and innovative learning approaches in preparing students for the evolving demands of the media and creative industries. The study's findings provide insights into how educational tools, such as enrichment books, can be pivotal in improving students' writing skills while also supporting the development of competencies that are essential for success in the modern workforce. This research is relevant for educators, curriculum developers, and policymakers looking to enhance the quality of journalism education by integrating creative and entrepreneurial skills into academic programs.